THE EFFECT OF COMPETENCE ON THE PERFORMANCE MODERATED BY JOB SATISFACTION (A Study on Radio Broadcasters in Malang) - ABIYYU BRILLIANDITYO (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study aims to examine and analyze the effect of radio broadcasters’ competence on their performance with job satisfaction as the mediation variable. This explanatory research attempts to explain the causal relationship between the variables through hypothesis testing. 46 respondent samples are selected through saturated sampling technique from a population of radio broadcasters in Malang. The selected samples meet the following characteristics: aged at least 17 years old, being an active broadcaster in a radio station in Malang, and having been experienced as the radio broadcaster for at least 6 months. The data are analyzed using PLS SEM with SmartPLS software 3.2.6. The research instrument is assessed by outer model, inner model, and hypothesis tests. The direct hypothesis test utilizes t-test, while the indirect hypothesis is tested by sobel test. The results of the analysis show that competence has positive and significant effect on the job satisfaction of the radio broadcasters in Malang. Furthermore, job satisfaction has positive and significant effect on the performance of the radio broadcasters in Malang.  In addition, competence positively and significantly influences the performance of radio broadcasters in Malang. Last, the indirect effect of competence on performance through job satisfaction of the radio broadcasters in Malang show a positive and significant result as well. Keywords: Competence, Job Satisfaction, Performance, Radio Broadcasters